PRODUCTION OF BIO-ADDITIVES FROM GLYCEROL IN THE PRESENCE OF HETEROGENEOUS CATALYSTS - Castanheiro, J (2014)
Glycerol is a by-product in the biodiesel production. For every 9 kg of biodiesel produced, about 1 kg of glycerol is formed. Due to the increase of biodiesel production, an increase of glycerol production has been observed. Consequently, it is imperative to find new applications for the excess of glycerol produced from biodiesel. The glycerol can be converted into oxygenated compounds by different reactions, such as esterification, etherification and acetalisation, which can be used as bio-additives. Traditionally, these reactions are carried out in the presence of homogeneous catalysts. However, due to environmental problems, the homogeneous catalysts have been replaced by heterogeneous ones, which can be separated from reaction mixture and reusable. In this work, the production of bio-additives from glycerol in the presence of solid acid catalysts will be review.